Outstanding Students on the Global Stage: The Role of Content-Based English Learning - Kuswanto, Welly (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Students' ability to compete in the global arena is essential in the era of globalization. Mastery of English, especially through a content-based approach (CBI), is seen as crucial as a bridge to international excellence. This study aims to analyze the role of content-based English learning in shaping Indonesian students who excel and compete in the global arena. Using a qualitative case study design, data were collected through in-depth interviews with students and lecturers, classroom observations, and document analysis at a university in Malang, Indonesia. Data were analyzed thematically. The main results showed that CBI significantly improved students' academic and professional communication abilities, including mastery of specific terminology and presentation skills. The optimal CBI design for international participation involves the integration of global materials and simulation of real situations. Despite challenges such as the availability of teaching materials, student enthusiasm and institutional support were great opportunities. It is concluded that CBI not only improves language proficiency, but also develops students' global competence and readiness to interact in international forums. This research contributes by filling the literature gap on how CBI in the Indonesian context can be a strategic instrument to achieve global excellence, recommending the development of more integrated curriculum and teaching materials.